PRINSIP PERHUBUNGAN AWAM MENURUT PERSPEKTIF ISLAM: PENELITIAN KONSEPTUAL: Principles of Public Relations Based on the Islamic Perspective: Conceptual Research - Ridzuan, Ahmad Al-Munzir; Kamri, Nor 'Azzah; Mohd Yusoff, Zulkifli (Jurnal Syariah, 2021)
Public relations are one of the essential elements for most of the organisations today. It is a center of focus in the organisations for channeling and disseminating the information both internally and internationally. Usually, public relations unit is the entity that responsible and directly involved in the public relations process. However, in the absence of a dedicated public relations unit, other people or units play a role in carrying out public relations responsibilities. In fact, most of the organisations use public relations to handle current issues or difficulties. Besides, it is used as one of the channels to publicize the achievements and successes achieved by the organisations. While conducting public relations, it might cause several issues such as non-transparency, interruption and inconsistencies. These should be avoided because they are not only destroying the social norms but also religious norms. Thus, this article will explain the fundamentals of Islamic public relations. Data are gathered through library study, as well as research on the Qur’an, Sunnah, and history. Next, it will be analysed using content analysis. Based on the findings, there are five elements of Islamic public relations: (1) create understanding, (2) protect the truth, (3) honor the promises, (4) use acceptable language and (5) take appropriate approach. The outcomes of this research will contribute to the development of knowledge in the field of public relations in general and Islamic public relations in particular.